A LOOK ON LITERACY HISTORIC AND CONTEMPORARY PROCESSES AND CHALLENGES - Frade, Isabel Cristina Alves da Silva (2022)
In the text, we discuss the historic and contemporary challenges regarding literacy. In the historic dimension, we problematize some out-of-school factors that explain the dissemination of literacy in Western countries and some elements that allow us to consider the relation between literacy and society in Brazil. In the contemporary dimension, we discuss the continuation of historic challenges to teach how to read and write, the need to think literacy in cultural and historic context involving the available technologies in each time. Furthermore, we consider some challenges of digital written culture to understand the changes and permanence of written culture, such as the use of supports; the dissemination of other semiotic systems; and the challenges to incorporate in the repertoire of those learning how to read and write the inherited manuscript and written culture, as well as digital written culture.